2020
DOI: 10.1080/20002297.2020.1771071
|View full text |Cite
|
Sign up to set email alerts
|

A nanocarrier system that potentiates the effect of miconazole within different interkingdom biofilms

Abstract: Background: Novel and new therapeutic strategies capable of enhancing the efficacy of existing antimicrobials is an attractive proposition to meet the needs of society. Objective: This study aimed to evaluate the potentiating effect of a miconazole (MCZ) nanocarrier system, incorporated with iron oxide nanoparticles (IONPs) and chitosan (CS) (IONPs-CS-MCZ). This was tested on three representative complex interkingdom oral biofilm models (caries, denture and gingivitis). Materials and methods: The planktonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…It should also be noted that only normal qPCR, and not live/dead qPCR, was used to quantify the bacterial and fungal load in the models following treatment. This live/dead methodology has been used with great effect to assess the level of “viability” of oral microorganisms in plaque samples and in vitro biofilm models [ 38 , 44 , 95 ]. Therefore, it could be that no changes were observed in the total bacterial or fungal load in this study, but there may have been reductions in the number of viable cells present in the biofilm (which could corroborate with the metabolic activity changes particularly for CHX treatment for example).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that only normal qPCR, and not live/dead qPCR, was used to quantify the bacterial and fungal load in the models following treatment. This live/dead methodology has been used with great effect to assess the level of “viability” of oral microorganisms in plaque samples and in vitro biofilm models [ 38 , 44 , 95 ]. Therefore, it could be that no changes were observed in the total bacterial or fungal load in this study, but there may have been reductions in the number of viable cells present in the biofilm (which could corroborate with the metabolic activity changes particularly for CHX treatment for example).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed that solubilized chitosan was effective in reducing the viability of three single-species biofilms containing Streptococcus mutans , Actinomyces naeslundii , and Enterococcus faecalis [ 54 ]. Our group has recently shown chitosan within a nanocarrier system to be effective against interkingdom biofilms representing caries (five species), gingivitis (seven species), and denture stomatitis (11 species) [ 55 ]. Here, we show with our optimized endodontic model that chitosan is particularly effective in inhibiting regrowth of a mixed-species biofilm model following physical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CDX-loaded nanocarriers may promote a higher antibiofilm effect of the drug, while lowering its toxicity toward human cells [ 142 ]. Magnetic NPs coated with chitosan were also used to load miconazole, a drug with both antibacterial and antifungal properties [ 143 , 158 ]. This formulation was further tested on three representative interkingdom oral biofilms (caries, denture, and gingivitis) [ 143 ].…”
Section: Novel Treatment Strategiesmentioning
confidence: 99%
“…Magnetic NPs coated with chitosan were also used to load miconazole, a drug with both antibacterial and antifungal properties [ 143 , 158 ]. This formulation was further tested on three representative interkingdom oral biofilms (caries, denture, and gingivitis) [ 143 ]. In all three models, nanocarriers containing miconazole significantly reduced the number of viable cells.…”
Section: Novel Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation